Slaying the Leviathan: Critical Jurisprudence and The Treaty of Waitangi - Upston-Hooper, K (Victoria University of Wellington Law Review, 1998)
This article considers the perspectives of four contributors to the current discourse on the Treaty of Waitangi: Professor Jane Kelsey, Dr Paul McHugh, Professor F M Brookfield and Moana Jackson. The jurisprudential underpinnings of each authors arguments are examined. The article focuses on the degree to which two new forms of jurisprudential thought, Critical Legal Studies and Critical Race Theory, have informed the Treaty discourse. The article concludes that, although such critical jurisprudence has yet to permeate New Zealand jurisprudence in any meaningful way, Critical Race Theory could help transform post-settler legal thinking. This article was awarded the Quentin-Baxter LLM prize in Public and International Law in 1997.